Cryptanalysis of RSA with Small Multiplicative Inverse of (p - 1) or (q - 1) Modulo e - PRATHA, ANURADHA KAMESWARI (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
In this paper, we mount an attack on RSA by using lattice based techniques implemented in the case when $p-1$ or $q-1$ have small multiplicative inverse less than or equal to $N^δ$ modulo the public encryption exponent $e$, for some small $δ$ and described the attack bounds for $δ.$